The Dispositif of the University Reform: The Higher Education Policy Discourse in Poland, 1st edition - Ostrowicka, Helena (Routledge, 2020)
The Dispositif of the University Reform presents a discourse analysis about transformations in higher education in Poland. Combining Foucauldian categories of discourse, dispositif and governmentality with contemporary changes in the area of science and higher education, it proposes an analysis of power in close connection with the development of knowledge.